The Influence of Transformational Leadership Style to Nurse Job Satisfaction and Performance in Hospital - Wijayanti, Kusumaningrum; Aini, Qurratul (Riviera Publishing, 2022)
The complexity of today's healthcare system challenges hospitals to provide safe, patient-oriented, and cost-effective services. Leadership style in an organization is one factor that plays an essential role in increasing or slowing down the interest and commitment of individuals in the organization. The transformational leadership style emphasizes moral principles, cooperation, and community together united in the privilege of human ethics. Job satisfaction of nurses is expected to improve their performance to create full service to patients. This literature review aims to determine the effect of transformational leadership style on job satisfaction and performance of hospital nurses. The method in this study is a literature review by searching for articles through the Ebscohost, Science direct, and Proquest electronic databases published from 2016-2021 and meeting the inclusion criteria. The review process uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: The results of this review obtained nine articles showing that the transformational leadership style has a positive influence on job satisfaction. Five reports show that leadership positively affects nurse performance in hospitals. Transformational leadership style influences job satisfaction and nurse performance in hospitals. Transformational leadership has more influence on nurse performance than transactional leadership in public hospitals. Nurses' job satisfaction is influenced by opportunity, structural empowerment, job attachment, work environment, and stress. At the same time, nurse performance is influenced by organizational commitment, employee empowerment, workload, motivation, stress, psychological safety, work attachment, and work environment.